The novel role of Yin Yang 1 in acute rejection of liver allografts through activation of dendritic cells - Chen, Yi; Wang, Jie; Hong, Liping; Wang, Hongtao; He, Wubing; Chen, Lihong (Frontiers in Immunology, 2025)
IntroductionAcute rejection is a critical complication after liver transplantation, contributing significantly to transplant dysfunction and recipient mortality. Yin Yang 1 (YY1), a zinc-finger transcription factor, has an undefined role in liver allograft acute rejection, despite its broad expression and regulatory potential in immune responses.MethodsTo investigate YY1's role, we used an MHC Class II-mismatched rat liver transplantation model. Allografts were harvested on post-transplant days 5 and 10 for YY1 expression analysis in inflammatory cells around recipient liver central veins. In vitro, dendritic cells (DCs) were transfected to overexpress YY1, and their surface markers (CD80, CD86, MHC II) and cytokine production (TNF-α, IL-6) were assessed. Naïve CD4+ T cells were co-cultured with YY1-overexpressing DCs to evaluate their polarization towards inflammatory phenotypes (IL-17, IFN-γ production).ResultsYY1 expression was elevated in inflammatory cells of allografts on days 5 and 10 post-transplant, correlating with increased serum transaminases and inflammatory cytokines. YY1-overexpressing DCs showed heightened expression of CD80, CD86, and MHC II, along with augmented TNF-α and IL-6 production. These YY1-activated DCs drove naïve CD4+ T cells to produce higher levels of IL-17 and IFN-γ, indicating polarization towards a proinflammatory Th17/Th1 phenotype.DiscussionYY1 promotes DC activation and naïve T cell polarization towards inflammatory phenotypes, thereby contributing to acute rejection in liver transplantation. Targeting YY1 may offer a therapeutic strategy to mitigate acute rejection and improve transplant outcomes. Further research is warranted to explore YY1's regulatory mechanisms and therapeutic potential in liver transplantation.